Religious moderation from the plains of the land of a seribu suluk: phenomenological experience from pesantren in Rokan Hulu Riau - Astuti, Daharmi; Tambak, Syahraini; Tarigan, Target; Afrinaldi, Afrinaldi; Harahap, Musaddad (UIR Press, 2026)
The expanding discourse on religious moderation in Indonesia has positioned Islamic educational institutions—particularly pesantren—as pivotal actors in cultivating balanced religious outlooks. Despite their historical role in fostering ummatan wasathan (a just and moderate community), pesantren are frequently problematized within public narratives as potential loci of radicalism, especially in regions such as Riau, which is often associated with relatively low levels of religious tolerance. This study aims to examine and conceptualize the model of religious moderation as practiced in pesantren, and to contribute to the development of Islamic Religious Education discourse grounded in empirical realities. Adopting a qualitative phenomenological approach, this research draws on data collected through in-depth interviews, participant observation, documentation, and literature review. The study focuses on two pesantren with supplementary insights from key stakeholders within the local Ministry of Religious Affairs. The findings demonstrate that pesantren in Rokan Hulu have substantively operationalized the principles of religious moderation, with no indication of radical or extremist orientations. The four core indicators—national commitment, tolerance, non-violence, and accommodation of local culture—are generally well embedded in institutional practices. However, the dimension of cultural accommodation requires further reinforcement to enhance contextual engagement and community acceptance. These practices are underpinned by foundational Islamic ethical values, including tawasuth (moderation), tawazun (balance), ‘adl (justice), and tasamuh (tolerance). This study is limited to two pesantren within a specific regional context, which may constrain the generalizability of the findings. Nevertheless, it offers important implications for policymakers, educators, and scholars by highlighting the need to strengthen culturally responsive moderation practices within Islamic education. This study provides an original phenomenological account of religious moderation grounded in the lived experiences of pesantren communities in a socio-culturally distinctive region. It advances the scholarly conversation by integrating local Islamic traditions with contemporary moderation frameworks, thereby offering a nuanced model for fostering inclusive and contextually relevant Islamic education.